2005
DOI: 10.1029/2004jc002485
|View full text |Cite
|
Sign up to set email alerts
|

Field observations of swash zone infragravity motions and beach cusp evolution

Abstract: [1] Fluid flows consistent with low-mode edge waves were evident in video observations of swash motions during a field experiment in which beach cusps developed on an initially smooth beach. As beach cusps grew, energy lying along low-mode dispersion curves increased. The most energetic edge-wave propagation direction changed from upcoast to downcoast as the orientation of the cusp horns rotated. These observations suggest a coupling between morphodynamics and hydrodynamics, and are evidence that beach cusp ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…This theory has been supported by several studies (e.g. Kaneko, 1985;Seymour and Aubrey, 1985;Sherman et al, 1993;Ciriano et al, 2005) and results in a predicted cusp spacing equal to:…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…This theory has been supported by several studies (e.g. Kaneko, 1985;Seymour and Aubrey, 1985;Sherman et al, 1993;Ciriano et al, 2005) and results in a predicted cusp spacing equal to:…”
Section: Introductionmentioning
confidence: 70%
“…Longuet-Higgins and Parkin, 1962;Sallenger, 1979). Beach cusps have a direct interaction with swash (Coco et al, 2003;Dodd et al, 2008;Ortega-Sánchez et al, 2008) and surf zone processes (Ciriano et al, 2005;Garnier et al, 2010). However, despite the extensive literature on beach cusps and the several proposed mechanisms of their formation, the particular conditions under which such features appear and evolve remain uncertain.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, the presence of finite amplitude cusps theoretically inhibits the edge waves (Guza and Bowen, 1975), and some experimental studies show that cusps can exist in the absence of edge waves (Masselink et al, 2004). Moreover, although Ciriano et al (2005) observed the coexistence of cusps and edge waves, there was no evidence that edge waves were standing, which is a key requisite of the edge wave mechanism. In this theory the cusps grow as a reaction to a hydrodynamical instability.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, infragravity motions dominate the run-up of water onto the beach face [Raubenheimer and Guza, 1996], and are associated with morphological features such as beach cusps [Ciriano et al, 2005] and flooding during storms. Farther offshore, infragravity motions contaminate ocean bottom seismology measurements used to detect tsunamis [Mofjeld et al 2001] and to predict microseisms .…”
Section: Suggested Applicationsmentioning
confidence: 99%